\(\frac{-3}{9}=\frac{-1}{3}\) ; \(2\frac{1}{2}=\frac{5}{2}\)
Ta thấy \(\frac{-1}{3}< 1\) ; \(\frac{5}{2}>1\)
=> \(\frac{-3}{9}< 2\frac{1}{2}\)
nha bnMèo Nhok Đinh
chúc bn học giỏi
C1 :\(\frac{-3}{9}\)và \(2\frac{1}{2}\)
\(\frac{-3}{9}=\frac{-6}{18}\)
\(2\frac{1}{2}=\frac{5}{2}=\frac{45}{18}\)
Vì \(\frac{45}{18}>\frac{-6}{18}\) nên \(2\frac{1}{2}>\frac{-3}{9}\)
C2 : \(2\frac{1}{2}=\frac{5}{2}\)
Vì \(\frac{-3}{9}\)là phân số âm và bé hơn 1
và \(\frac{5}{2}\) là phân số dương và lớn hơn 1
nên \(\frac{5}{2}>\frac{-3}{9}\) nên \(2\frac{1}{2}>\frac{-3}{9}\)
K mk nha, mk làm nhanh nhất thật 100 % nhá